On the Global Asymptotic Stability and 4-Period Oscillation of the Third-Order Difference Equation - M. E. Erdogan (Journal of Applied Mathematics)
The main objective of this paper is to study the global behavior and oscillation of the following third-order rational difference equation xn+1=αxnxn−1xn−2/βxn−12+γxn−22, where the initial conditions x−2,x−1,x0 are nonzero real numbers and α,β,γ are positive constants such that α≤β+γ. Visual examples supporting solutions are given at the end of the study. The figures are found with the help of MATLAB.